VD_FINDINFO ML / 2011 / 127 vom 7. April 2011 - VD Tribunal cantonal (2011)
MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE, OBLIGATION D'ENTRETIEN, ENFANT, SOCIÉTÉ SIMPLE, MAJORITÉ{ÂGE}, CONSORITÉ | 530 CO, 543 CO, 67 al. 1 ch. 1 LP, 80 al. 1 LP, 80 al. 2 ch. 1 LP